2014
DOI: 10.1371/journal.pone.0084746
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Survival Signaling from Both Jak2-V617F and Lyn Involving GSK3 and mTOR/p70S6K/4EBP1 in PVTL-1 Cell Line Newly Established from Acute Myeloid Leukemia Transformed from Polycythemia Vera

Abstract: The gain of function mutation JAK2-V617F is very frequently found in myeloproliferative neoplasms (MPNs) and is strongly implicated in pathogenesis of these and other hematological malignancies. Here we report establishment of a new leukemia cell line, PVTL-1, homozygous for JAK2-V617F from a 73-year-old female patient with acute myeloid leukemia (AML) transformed from MPN. PVTL-1 is positive for CD7, CD13, CD33, CD34, CD117, HLA-DR, and MPO, and has complex karyotypic abnormalities, 44,XX,-5q,-7,-8,add(11)(p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…As it is known that in B cells, the Tyr273 residue within ITIM of FcgRIIb2 is phosphorylated by LYN to inhibit cell proliferation (24), we started to analyze the kinase activity of LYN in neuronal cells after exposure to oAb . LYN activity is often determined by the level of the autophosphorylation at the Tyr397 residue (25). Treatment of both primary mouse cortical neurons and SH-SY5Y human neuroblastoma cells with oAb 1-42 greatly enhanced the autophosphorylation of LYN at Tyr397 (Fig.…”
Section: Lyn Kinase Is Activated In Neuronal Cells By Oab Treatment Amentioning
confidence: 99%
“…As it is known that in B cells, the Tyr273 residue within ITIM of FcgRIIb2 is phosphorylated by LYN to inhibit cell proliferation (24), we started to analyze the kinase activity of LYN in neuronal cells after exposure to oAb . LYN activity is often determined by the level of the autophosphorylation at the Tyr397 residue (25). Treatment of both primary mouse cortical neurons and SH-SY5Y human neuroblastoma cells with oAb 1-42 greatly enhanced the autophosphorylation of LYN at Tyr397 (Fig.…”
Section: Lyn Kinase Is Activated In Neuronal Cells By Oab Treatment Amentioning
confidence: 99%
“…Targeting mTOR has also demonstrated positive anti-MPN effects as a single agent and in combination with JAK2 inhibition. 45,[65][66][67][68][69] The potency of the combination of INCB053914 and ruxolitinib was also manifested in in vivo MPN models driven by aberrant JAK2 signaling. The combination of INCB053914 and ruxolitinib antagonized the growth of SET2 cell xenograft tumors at doses of each drug that had little to no effect as monotherapies ( Figure 6A).…”
Section: Incb053914 and Ruxolitinib Suppress Jak2 V617f -Driven Tumormentioning
confidence: 99%
“…A persistently active mutant of STAT5 (STAT5a s711F ) associates with Gab2 in myeloid leukemias and promotes growth in vitro via the activation of AKT activation ( 66 ). Nagao T et al found that apoptosis may be suppressed in PVTL-1 cells, an AML cell line, through inactivation of GSK3 by Lyn, and of JAK2-V617F and is also suppressed by the activation of STAT5 by JAK2-V617F ( 67 ). Tyrosine-phosphorylated-STAT5 can be tracked using flow cytometry or immunostaining and is a biomarker associated with poor prognosis in patients with juvenile myelomonocytic leukemia (JMML) ( 66 ) and AML ( 68 ).…”
Section: Gab2 In Cancermentioning
confidence: 99%